THE EFFECT OF LEADERSHIP, MOTIVATION, AND SERVICE QUALITY OF VILLAGE HEAD ON COMMUNITY AWARE IN PAYING TAXES ON LAND BUILDING IN LUWU DISTRICT - Ikhrar Septa Margono; Musran Munizu; Julius Jilbert (Scientia Integritas Utama, 2023)
This study aims to: (1) find out and analyze the influence of the variables of leadership, motivation, and service quality of village heads on public awareness in paying taxes on land and building in Luwu district; and (2) find out and analyze the variables that have dominant influence. The method of analysis used in this study was the multiple linear regression analysis. The results are: (1) The variables of leadership, motivation, and service quality have a significant influence on community awareness in paying taxes on land and building; (2) The service quality variable has a dominant influence on the community awareness; (3) Based on the results of data analysis with multiple linear regression, leadership, motivation, and service quality have an influence of 14.4%, 31.8%, and 44.1% respectively; (4) Based on the result of determination coefficient test (R), 78.2% of community awareness can be explained by the variables of leadership, motivation, and service quality. The rest 21.8% can be explained by other causes that are not discussed in the study.